Effect of Lamotrigine on the EEG - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The effects of add-on lamotrigine (LTG) therapy on EEG paroxysmal abnormalities and background activity are evaluated retrospectively in 53 children and adolescents (mean age 12.5 years) with refractory epilepsy followed at Children's Hospital, Boston, MA.